Gambaran Pengetahuan Cuci Tangan dan Memakai Masker di Masa Pandemi pada Anak Sekolah Kelas 4-5 di SD Negeri Dolok Nagodang Tahun 2021 - Lindawati Simorangkir; Amnita Ginting; Marni Olypia Sinaga (Journal of Indah Science and Clinic, 2022)
Knowledge of hand washing and wearing masks is an action or behavior in school children that comes from experience they have or from other sources such as parents, teachers, friends and others that can reduce the spread of Covid-19 disease in order to protect themselves or control themselves from droplets. This study aims to describe the knowledge of hand washing and wearing masks during in pandemic in grade 4-5 school children at SD Negeri Dolok Nagodang Kecamatan Uluan. This research is a quantitative research and uses a total sampling. The subjects in this study were students in grade 4-5 as many 30 people. Data collection was carried out by distributing questionnaires offline. Data analysis using univariate. The results showed that of the 30 respondents who had knowledge of washing hands and wearing masks in good category, there were 22 respondents (73,3%) and knowledge of washing hands and wearing masks with sufficient category was 8 respondents (26,7%). Knowledge of washing hands and wearing masks in school children is increashing well.